Financial Diagnosis Using CAMEL Model: Public versus Private Banks in Bangladesh - Akter, Aklima (American Journal of Trade and Policy, 2017)
The purpose of this paper is to empirically analyze the financial statement of two selected banks (One bank from the public sector and another one from the private) in Bangladesh during 2010-14. This study highlights ranking of two banks for their performance on CAMEL (Capital Adequacy; Asset Quality; Management Quality; Earnings Ability; and Liquidity) ratios. During the year Empirical results suggest that 2010-2014 NCCBL has scored better position of all the ratios except EPS, liquid assets to total assets and liquid assets to total deposits compared to JBL. By considering all of the parameters of CAMEL, NCCBL is the highest position assessed by the CAMEL Model because of its performance on the CAMEL ratios compared to JBL. JBL is lower position compared to NCCBL under the study because of its poor performance on the CAMEL ratios. The ultimate findings of the study indicate that JBL should improve the weaknesses of the CAMEL which ultimately improve the bank’s overall performance. The findings of the paper will enable the practitioners and analysts to understand financial statement analysis in a depth manner.